Intranasal Delivery of RIG-I Agonist Drives Pulmonary Myeloid Cell Activation in Mice - Nair, Sajith; Wu, Yilun; Nguyen, Trinh Mai; Fink, Katja; Luo, Dahai; Ruedl, Christiane (Frontiers in Immunology, 2022)
Viral respiratory infections cause substantial health and economic burden. There is a pressing demand for efficacious vaccination strategies and, therefore, a need for a better understanding of the mechanisms of action of novel potential adjuvants. Here we investigated the effect of a synthetic RIG-I agonist, the dsRNA hairpin 3p10LA9, on the activation of pulmonary myeloid cells. Analysis of early innate immune responses revealed that a single intranasal 3p10LA9 dose induces a transient pulmonary interferon-stimulated gene (ISG) and pro-inflammatory cytokine/chemokine response, which leads to the maturation of three distinct dendritic cell subpopulations in the lungs. While lung resident dendritic cell decrease shortly after 3p10LA9 delivery, their numbers increase in the draining mediastinal lymph node, where they have migrated, maintaining their activated phenotype. At the same time, dsRNA hairpin-induced chemokines attract transiently infiltrating monocytes into the lungs, which causes a short temporary pulmonary inflammation. However, these monocytes are dispensable in controlling influenza infection since in CCR2 deficient mice, lacking these infiltrating cells, the virus load was similar to the wild type mice when infected with the influenza virus at a sublethal dose. In summary, our data suggest that intranasal delivery of dsRNA hairpins, used as a RIG-I targeting adjuvant, represents an attractive strategy to boost type I inteferon-mediated lung dendritic cell maturation, which supports viral reduction in the lungs during infection.